Heterophase quasicrystalline interfaces and their characterization - Mandal R.K. (My University, 2025)
The characterization of heterophase interfaces in icosahedrally related systems cannot be accomplished by the available three-dimensional crystalline terms owing to lack of periodicity of at least one of the phases constituting the boundary. The purpose of this communication is to show that the existing method of interface characterization in terms of registry of the two underlying lattices can be recovered for quasiperiodic cases by extending the concept to six- dimensional hyperspace. This has been demonstrated by the method of characterizing the interface between icosahedral and decagonal quasicrystals found in Al-Pd-Mn system. © 1999 Taylor & Francis Group, LLC.